State of the art about domain analysis in the Brazilian Information Science Field - Almeida, Josiana Florêncio Vieira Régis de; Dias, Guilherme Ataíde (Faculdade de Filosofia e Ciências, 2019)
This article presents the state of the art on the production of knowledge related to Domain analysis in Information Science delimited within the scope of Brazilian research. 46 documents were analyzed (excluding the duplication of the records found in the databases), classified in articles of periodicals, doctoral theses, master dissertations, oral communications of ENANCIB and publications of another nature with publication date between 2013 and 2018. The search of the publications was carried out by means of the identification of the descriptors in Portuguese "Análise de domínio" and "Ciência da Informação" and in English "Domain analysis" and "Information Science" in the summary, title, keywords. For the analysis of the documents, the eleven approaches or analysis tools established by Hjørland (2002) were used in the definition of a domain to classify the works and to facilitate the understanding of the use of the theoretical-methodological foundations of the Domain Analysis of the recovered documents. It concludes that the researches found showed a strong tendency for bibliometric studies of domain analysis (with citation analysis, co-citation, co-occurrence and network analysis) and for the techniques of organization and representation of knowledge. It is recommended to use the domain analysis method in the construction of Knowledge Organization Systems, especially in the elaboration of special classifications in Information Science domains.